(untitled) (Canadian Journal of Native Studies, 2026)
Abstract The Indigenous mental health crisis in Canada must be contextualized with discussions on race and colonialism within population health research. This research uses nationally representative data from the 2015-2016 Canadian Community Health Survey to investigate the mental health service utilization of Indigenous populations relative to non-Indigenous populations. Preliminary findings suggest an underutilization of mental health services by Indigenous people because although they are more likely than non-Indigenous people to possess characteristics related to an increased likelihood of consulting a mental health professional, findings show that Indigenous peoples access mental health services at similar rates as non-Indigenous peoples.